KAJIAN PEMASANGAN LIGHTNING ARRESTER PADA SISI HV TRANSFORMATOR DAYA UNIT SATU GARDU INDUK TELUK BETUNG - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
Generally, The power centers are connected to the air transmission line, and the airborne transmission channel is susceptible to disturbances that are affected from outside the system, one of which is a lightning strike. Lightning strikes are harmful to the components present in the central power supply. And therefore, the protection from the lightning strikes is required, so that the components in the power center is not damaged when exposed to lightning surges. In this research we discussed the power transformer protection (60MVA) on the Teluk Betung substation so that the power transformer is safe from the over voltage caused by the lightning surge. The specification of the arresters mounted on the HV side of the power transformer unit one of Teluk Betung substation with nominal voltage of 144 kV has been in accordance with the system requirements. The maximum distance between the arrester and the allowable power transformer is 28.5 meters. Distance in the field is 3 meters, the voltage that arrives at the power transformer is 480 kV and still below the Basic insulation level of the transformer, so that the protection of the power transformer against the lightning surge is very good.